Contextual effects of community capacity as a predictor for adolescent alcohol, tobacco, and illicit drug use: A multi-level analysis - Vera Birgel; Dominik Röding; Maren Reder; Renate Soellner; Ulla Walter (Elsevier, 2023)
Adolescent substance use is a major public health issue that can result in enduring physical, psychological, and social consequences. This study seeks to examine the relationship between community capacity for prevention and the 4-week prevalence rate of substance use, including tobacco, alcohol, other drugs, and binge-drinking, among students in Germany ranging from grades 5 to 11. This study employed a cross-sectional design and used baseline data from 28 communities participating in the CTC-EFF study. The sample consisted of 7210 students who were surveyed about their substance use behavior. Additionally, 158 local key informants were surveyed on ten capacity domains, which included commitment, knowledge and skills, resources, leadership, inclusiveness, prevention collaboration, sectoral-collaboration, cohesion, problem-solving skills, and needs orientation. Furthermore, a total capacity score was calculated as the mean of the ten capacity domains. To examine the associations between community capacity and substance use behavior, logistic multi-level models were utilized. The analysis shows a negative association between community capacity (total score) and any substance use (OR = 0.28, 95% CI 0.12-0.56). Specifically, higher levels of total community capacity are associated with lower odds of alcohol use (OR = 0.30, 95% CI 0.13-0.80), tobacco use (OR = 0.09, 95% CI 0.01-0.60), and binge-drinking (OR = 0.67, 95% CI (0.46-0.99). Further analyses of distinct community capacity domains indicate that higher levels of sectoral-collaboration (OR = 0.62, 95% CI 0.37-0.97), knowledge and skills (OR = 0.74, 95% CI 0.40-0.79), resources (OR = 0.52, 95% CI 0.36-0.76), and problem-solving skills (OR = 0.71, 95% CI 0.36-0.89) are associated with lower odds of any substance use. The study findings suggest that community capacity is associated with substance use behavior, emphasizing the importance of capacity building in interventions targeting the reduction of substance use among adolescents.